Combined heat source and zero mass flux features on magnetized nanofluid flow by radial disk with the applications of Coriolis force and activation energy. (July 2021) - Ullah, Ikram; Ullah, Refat; Alqarni, M.S.; Xia, Wei-Feng; Muhammad, Taseer
Abstract: The nanomaterials are more efficient in different areas like in pharmacy industry, cooling of compressors, engines, heating materials, damage cells destruction and brain tumors etc. The foremost aim of the this communication is to scrutinize the effects of activation energy on the nanofluid flow of an infinite, rotating and stretchable disk in radial direction with thermal heat source (THS) and the exponential space heart source (ESHS). Brownian and thermophoresis diffusions are countered to study the nanofluid. The Coriolis force and effects of radial magnetism are deployed. Nonlinear Boungiorno model is utilized. The modeled PDEs are converted to system of ODEs via proper variables. The obtained system is approximated through NDSolve technique. Features of various variables on flow profiles are examined and outcomes are declared via curves and tables. It is investigated that ESHS is highly influential than THS on fluid temperature. Furthermore it is found that activation energy enhances the concentration.